Exploring the impact of a daily sport uniform policy in primary schools: a qualitative study with students and teachers - Carly Gardner; Carly Gardner; Carly Gardner; Carly Gardner; Cassandra Lane; Cassandra Lane; Cassandra Lane; Cassandra Lane; Alix Hall; Alix Hall; Alix Hall; Alix Hall; et al. (Frontiers in Sports and Active Living, 2025)
BackgroundIdentifying effective, scalable interventions that promote physical activity in children, is a public health priority. Implementing daily sport uniform wear (activity enabling uniforms) in schools represents one such option. This qualitative study explored the perspectives of students and teachers at primary schools (elementary schools) where a daily sport uniform policy had been implemented.MethodsWe used a pragmatic, exploratory qualitative study design with data collected from participants in the intervention arm of a randomised controlled trial. One-on-one interviews with teachers were conducted following a semi-structured guide and student focus groups used an activity-based structure. Thirteen students and two teachers from two schools participated in data collection between August–September 2023. The two data sets (students and teachers) were analysed inductively using Framework Analysis identifying three overarching themes.ResultsThe first two themes were synthesised from both data sets while teacher's perspectives primarily contributed to the final theme. First, daily sport uniform wear was highly accepted, due to their visual appeal, simplicity and cost-savings relative to formal uniforms. Second, daily sport uniform wear positively impacted students by enabling physical activity, enhancing wellbeing, providing comfort, and promoting equity. Third, formal uniforms were perceived as the norm, associated with tradition and societal expectation.ConclusionThis study deepens our understanding of the potential health and wellbeing benefits a daily sport uniform policy may have and highlights barriers such as traditions persist in school settings. Policy sustainment may require considered implementation support and consulting students in uniform designs and options.